Production and efficiency : the case of the Australian Rugby League : a thesis submitted in partial fulfilment of the requirements for the degree of Masters of Applied Economics at Massey University - Richardson, Sam (Massey University, 1999)
What matters in the "production" of a game of rugby league? This analysis finds that several game-specific inputs (such as successful goal-kicking percentage, inherent team strength, and momentum of results) in the generation of a game outcome are statistically significantly different from zero at the 10% level or lower. This study also looks closely at measures of productive efficiency, including stochastic frontier modelling and data envelopment analysis (DEA). Panel data from the 1995, 1996 and 1998 National Rugby League (NRL) regular seasons are used to formulate average production functions and stochastic production frontier models and their respective measures of efficiency. It is found that many Sydney-based teams performed relatively more efficiently when compared to non-Sydney teams in 1998. There also appears to be evidence of a "weaker teams bringing the stronger teams down to their level" effect due to differences in point-scoring efficiency and game outcome efficiency in 1998.
Keywords: Australia; Rugby League football -- Economic aspects; Production functions (Economic theory); Case studies; Industrial efficiency; Australian Rugby League